2009
DOI: 10.1158/1055-9965.epi-08-0418
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in How Parents Are Learning about the Human Papillomavirus Vaccine

Abstract: Background: Differential access to basic health information may contribute to persistent cervical cancer disparities. We examined whether human papillomavirus (HPV) vaccine awareness, HPV knowledge, and use of information sources about the vaccine differ by sociodemographic characteristics associated with cervical cancer. Methods: Study participants (n = 889) were caregivers of adolescent girls ages 10 to 18 years living in southeastern North Carolina. Analyses simultaneously controlled for caregivers' gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
134
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(148 citation statements)
references
References 46 publications
10
134
3
1
Order By: Relevance
“…Knowledge related to HPV and the HPV vaccine may be a key predictor of HPV vaccine uptake. A few studies have demonstrated that parents with higher levels of HPV and HPV vaccine knowledge are more likely to have given permission for their daughters to receive the HPV vaccine 26,27 and are more likely to support vaccine uptake for their daughters. 28,29 Note that these studies have included very few or no U.S. Latino parents and were cross-sectional in design.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge related to HPV and the HPV vaccine may be a key predictor of HPV vaccine uptake. A few studies have demonstrated that parents with higher levels of HPV and HPV vaccine knowledge are more likely to have given permission for their daughters to receive the HPV vaccine 26,27 and are more likely to support vaccine uptake for their daughters. 28,29 Note that these studies have included very few or no U.S. Latino parents and were cross-sectional in design.…”
Section: Discussionmentioning
confidence: 99%
“…35 In brief, nine counties clustered in southeastern North Carolina met study inclusion criteria (higher than average cervical cancer rates and ⩾ 20% African-American residents). After matching eligible counties on population size, proportion of African American residents, and cervical cancer rates, we randomly selected four rural counties to study (Duplin, Harnett, Sampson, and Wayne counties), and chose the one urban county (Cumberland) in this region.…”
Section: Methodsmentioning
confidence: 99%
“…Of 1,220 eligible parents, 889 (73%) parents participated. 35 The University of North Carolina institutional review board approved the study protocol.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, the media was cited as a source of information about the HPV vaccine (Gardasil), and vaccine uptake was associated with media use (including the use of print media) (Hughes et al, 2009). While not intended to be health education material, newspaper articles are a leading source of publicly available health information (MacDonald & Hoffman-Goetz, 2002).…”
Section: Introductionmentioning
confidence: 99%